Comparative Analysis of Vascular Cell Differentiation From Peripheral Blood Mononuclear Cell- and Urine-Derived Induced Pluripotent Stem Cells - Julia Deinsberger; Silvio Holzner; Sophie Bromberger; Philipp Foessleitner; Dominik Wiedemann; Bernhard Winkler; Natalia Krajic; Sophia Aligianni; Elisabeth Stein; Jennifer Volz; Zahra Mazidi; Regina Grillari; et al. (Hindawi Limited, 2024)
Conclusions: This study presents a comprehensive comparative analysis of functionally differentiated ECs and VSMCs derived from PiPSCs and UiPSCs, providing critical insights into the expression patterns and phenotypic transitions during differentiation. Our findings enhance the understanding of distinct molecular signatures in iPSCs from different sources and their progeny.